Using ethnography techniques in developing a mobile tool for requirements elicitation - Shahidi, S.; Kasirun, Z.M. (2009)
Requirements Elicitation is the process of discovering, extracting and gathering requirements for a system through communication with the stakeholders. Very often the process is carried out by observing the workplace and analyzing their needs at the work context. Ethnography, it is an elicitation technique that supports context-aware requirements elicitation. Common tools used in requirements elicitation process are mostly desktop-based which decrease the mobility features of bringing them to workplace. Recent advances in mobile computing technologies intend that mobile devices have the potential to support elicitation activities in the workplace. The aim of this research is to develop a mobile tool to support ethnography-based techniques to help the analysts directly observe the stakeholders need and help them in better understanding the system requirements. This paper describes the ongoing research and presents the progress so far